2019
DOI: 10.12688/f1000research.17572.1
|View full text |Cite
|
Sign up to set email alerts
|

­­Statins in the perioperative period

Abstract: In this review, we discuss clinical evidence-based data regarding the potential benefit of statin therapy in the perioperative period of non-cardiac surgery. Results from meta-analyses of prospective observational studies have provided conflicting evidence. Moreover, comparison among studies is complicated by varying data sources, outcome definitions, types of surgery, and preoperative versus perioperative statin therapy. However, results of two recent large prospective cohort studies showed that statin use on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Among the potential advantages of this particular drug is that statins are considered safe and their effect on WPBs (at least in vitro) is fast (24 hours), compared to their effects in reducing cholesterol levels, which require significantly longer to stabilize 36 . Indeed, statins have been successfully exploited perioperatively 20,37,38 . These in vitro proof‐of‐principle studies using an experimental model provide a foundation from which the concept could be expanded to in vivo models and then to clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Among the potential advantages of this particular drug is that statins are considered safe and their effect on WPBs (at least in vitro) is fast (24 hours), compared to their effects in reducing cholesterol levels, which require significantly longer to stabilize 36 . Indeed, statins have been successfully exploited perioperatively 20,37,38 . These in vitro proof‐of‐principle studies using an experimental model provide a foundation from which the concept could be expanded to in vivo models and then to clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The randomized prospective LOAD (Lowering the risk of Operative complications using Atorvastatin loading Dose) trial also failed to show a reduction in major cardiovascular complications when a short-term course of atorvastatin was initiated in statin-naïve patients undergoing non-cardiac surgery [6]. Initiating statins in statin-naïve patients undergoing non-cardiac surgery needs to be evaluated with further trials [59]. This failure of atorvastatin to reduce cardiovascular events in the LOAD trial is not really surprising, given that most perioperative MI is precipitated by sympathetically mediated tachycardia from the stress response to surgery rather than by plaque instability [1].…”
Section: Opioidsmentioning
confidence: 99%
“…Statin use has also been shown to reduce mortality and shorten the length of hospital stay (LOS) in the same patient population [ 14 – 16 ]. It has been suggested that surgical patients should resume statin therapy in the perioperative period, particularly patients with atherosclerotic cardiovascular disease [ 17 ]. The goal of this study was to evaluate the effects of perioperative lipid-lowering medications on the incidence of postoperative adverse events and improving both short- and long-term outcomes in patients undergoing CABG/CABG with other procedures.…”
Section: Introductionmentioning
confidence: 99%